Non-linear behaviour of one-bay steel frame with semi-rigid connections - 555187 Ahmad Burhanuddin Abdul Rahman; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Awam (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references